2014
DOI: 10.1038/bjc.2014.317
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of the neutrophil-to-lymphocyte ratio in patients with small-cell lung cancer

Abstract: Background:The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are prognostic factors for various types of cancer. In this study, we assessed the association of NLR and PLR with the prognosis of small-cell lung cancer (SCLC) in patients who received the standard treatment.Methods:We retrospectively reviewed patients who were diagnosed with SCLC and treated with platinum-based chemotherapy between July 2006 and October 2013 in Gyeongsang National University Hospital Regional Cancer C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
135
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(157 citation statements)
references
References 43 publications
12
135
1
1
Order By: Relevance
“…PNI is not commonly used as a score for the measurement of systemic inflammatory responses, and a study of hepatocellular carcinoma (HCC) found that PNI was an independent and externally validated predictor of poor OS in patients with HCC (Pinato et al 2012). Only two studies have focused on the value of NLR for prognosis in SCLC, with the results indicating that elevated NLR could predict worse OS and PFS (Kang et al 2014;Wang et al 2014). There is, therefore, a lack of data from studies with adequate sample sizes and multiple inflammation-based scores.…”
Section: Discussionmentioning
confidence: 99%
“…PNI is not commonly used as a score for the measurement of systemic inflammatory responses, and a study of hepatocellular carcinoma (HCC) found that PNI was an independent and externally validated predictor of poor OS in patients with HCC (Pinato et al 2012). Only two studies have focused on the value of NLR for prognosis in SCLC, with the results indicating that elevated NLR could predict worse OS and PFS (Kang et al 2014;Wang et al 2014). There is, therefore, a lack of data from studies with adequate sample sizes and multiple inflammation-based scores.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies of advanced cancers, elevated NLR was a strong prognostic factor. 4,8,11,13,14,16,19,22,27,34 The role of the host inflammatory response in determining tumor spread is increasingly recognized. The association between elevated NLR and poor prognosis has several possible explanations.…”
Section: Figmentioning
confidence: 99%
“…15,35 A systematic inflammatory response leads to changes in the relative levels of circulating white blood cells, resulting in an increase in neutrophils and a decrease in lymphocytes with the progression of cancer. 25 Recently, an association was reported between a high neutrophil-to-lymphocyte ratio (NLR) and shorter survival time in patients with various cancers, 4,8,11,13,14,16,19,22,27,34 including glioblastoma. 3,12,18 However, the value of preoperative NLR in the assessment of candidates for resection for brain metastasis has not been evaluated.…”
mentioning
confidence: 99%
“…Therefore, it is not surprising that neutrophils, a key inflammatory cell type, can be mobilized and recruited to tumors. In fact, aberrant accumulation of neutrophils has been documented in a wide variety of tumors and is often associated with poor clinical outcomes (4)(5)(6)(7)(8)(9)(10)(11). Emerging evidence also suggests that neutrophils, in response to signals derived from cancer cells or stromal cells, can alter their phenotypes and migration routes and also release factors that act on tumor cells and other cell types (e.g., endothelial cells and immune cells), which we review in the following sections.…”
Section: Introductionmentioning
confidence: 99%